Analisis Kebijakan Pengelolaan Keuangan Sektor Publik dalam Mewujudkan Good Governance di Pemerintah Kota Gresik - Diva Noviant Fajar; Moch. Roffiqul Pradana; Sandy Azzurri (Journal of Economics Development Issues, 2023)
Gresik City is a city that is experiencing very rapid economic growth on the basis of the dynamics of capital circulation in the economic market and political mainstream. The process of implementing state power in carrying out the provision of public goods and services is part of good governance. In order for Good Governance to be successful, it requires commitment from all parties, namely the government and society. Therefore this study aims to determine the management of the public sector in realizing Good Government in the Gresik City area. The method used in this research is descriptive qualitative. The data used in writing is qualitative data, namely data in the form of information or explanations from authorized parties such as decisions of the directors, a brief history of the company, organizational structure and description of their duties, and other data relevant to the object of writing. The results of the research show that the regional government of Gresik has implemented the principles of good governance, although not optimal. This can be seen from the existence of legal supremacy, the ease of accessing information, the efforts to provide good service to the community, and being accountable for all its performance.